COMPARISON OF LASER AND PNEUMATIC LITHOTRIPSY FOR MID AND LOWER URETERAL STONES: “AN ANALYTICAL REVIEW” AT TERTIARY CARE CENTER - RAVIKUMAR JADHAV; THAKAPPA NG; RAVIRAJ RAYKAR; SHIVARATNA MAHADIK (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Management of large lower and mid ureteric stones represents a treatment challenge. The main objective of stone treatment is to achieve the highest stone-free rate with minimal morbidity. Available modalities are medical therapy, open surgery, laparoscopic surgery, endoluminal surgery and extracorporeal shock wave lithotripsy (ESWL). After the invention of uretero-renoscopy (URS) and ESWL in 1980s, there has been a paradigm shift in the treatment modality of ureteric calculus from open surgery to endoluminal and non-invasive method. There are various modalities for stone fragmentation in URS – electrohydrolic lithotripsy, pneumatic. Ultrasonic, laser and dual energy source (Ultrasound+Pneumatic) Lithotripsy. Both laser lithotripsy (LL) and pneumatic lithotripsy (PL) have favourable outcomes The aim of this study was to compare efficacy of pneumatic versus laser lithotripters for Mid and lower ureteric calculi in regional population at KIMS, Hubballi. Methods: This was a prospective comparative study done in 116 cases of mid and lower ureteric calculi (58 in PL and 58 in LL) at karnataka institute of medical sciences, Huballi from May 2022 to November 2022. Patients were randomly divided into two groups: Group 1 had PL, while Group 2 had lithotripsy using a laser energy source. For PL group, 0.8 and 1 mm probe was passed through working channel of URS. LL was performed using a 100- W holmium:yttriumaluminium-garnet (YAG)-pulsed laser machine, with 365 μm fibres. Complications were graded according to the Clavien-Dindo Grading System. Results: In all, 116 patients (78 male and 38 female) with a mean age of 36.21 years were included in the study, Varying from 18 to 75 years. In group one 58 patients under went PL out of which 41 were males and 17 were females. In group two 58 patients under went LL out of which 37 were males and 21 were females. In group one (PL) mean operative with SD was 42.10±(10.16) min, and in group two (LL). Mean operative with SD was 46.78±(9.36) min, with p=0.011, which was statistically significant. Mean hospital stay ±SD (days) in PL group was 2.69±(0.730) days, and in group two LL mean hospital stay ±SD (days) was 2.40±(0.591) with p=0.019, which was statistically significant. In group one out of 58 patients, 11 patients had stone migration with % of an 18.96% and in group two out of 58 patients 2 patient had stone migration of, with % of 3.44%, with p=0.008, which is statistically very significant. Post operatively 7 patients in group one needed auxillary procedures, 3 patients needed ESWL, 3 patients needed. Re URSL and one patient needed bladder clot evacuation with DJ stenting, In all these patients stone size was larger than 15 mm, In Group 2 no patient needed Auxillary procedure, with p=0.003 which is statistically significant. Conclusion: Both pneumatic and LL are standard and safe techniques for the management of lower and mid ureteric calculi. Our study showed LL had less stone migration, and no need for reintervention.